DEVELOPMENT OF LETTER CARD LEARNING MEDIA USING QR CODE FOR TEACHING LETTER RECOGNITION IN CHILDREN WITH DYSLEXIA AT UPT SPF SD INPRES MACCINI BARU MAKASSAR - Dynasti, Reza Hadiwijaya; Pristiwaluyo, Triyanto; Hadi, Purwaka; Bastiana, Bastiana (Humano: Jurnal Penelitian, 2024)
This study aims to: (1) Determine the results of the analysis of teacher needs for letter card learning media with QR Code at UPT SPF SD Inpres Maccini Baru Makassar, (2) Determine the process of developing Letter Cards with QR Code Technology for Letter Recognition in Children with Dyslexia at UPT SPF SD Inpres Maccini Baru Makassar, (3) Evaluate the effectiveness of using Letter Cards with QR Code Technology for Letter Recognition in Children with Dyslexia at UPT SPF SD Inpres Maccini Baru Makassar. This study used the Research and Development (RnD) method with the Borg and Gall development model modified by the researcher. The product testing was validated by 1 subject matter expert and 1 media expert, and the developed learning media were distributed. The data analysis method used was quantitative descriptive analysis technique with predetermined score distribution and category scale. The validation results of the learning media are: (1) Subject matter expert assessment is very feasible with a percentage of (95.05%). (2) Media expert assessment is very feasible with a percentage of (94.64%). Based on these results, the letter card learning media using QR Code that has been developed is suitable for use as a learning guidance media to train dyslexic students in recognizing and distinguishing letters at UPT SPF SD Inpres Maccini Baru Makassar.